PRONOMINA PADA KARANGAN CERITA FANTASI SISWA - Hikmah Nur Azizah; Hilda Hilaliyah; Memmy Dwi Jayanti (Universitas Pamulang, 2021)
Abstract This study aims to analyze the use of types of pronouns in fantasy story compositions of seventh grade students of SMP Harjamukti Depok. This type of research is descriptive qualitative. The data collection technique used was note reading technique. Analysis of the data used the split and match methods. The results of this study indicate that the use of personal prounouns is more dominant than other pronouns. This is because the personal pronouns has the potential and plays a role in developing essays that tell humans as characters, especially in fantasy stories. Keywords: Pronouns, fantasy stories, student essays. Abstrak Penelitian ini bertujuan untuk mengetahui dan menganalisis penggunaan pronomina pada karangan cerita fantasi siswa kelas VII SMP Harjamukti Depok. Metode yang digunakan adalah metode kualitatif sehingga bersifat deskriptif dan cenderung menggunakan analisis. Sumber data yang digunakan adalah karangan cerita fantasi siswa kelas VII SMP Harjamukti Depok sebagai acuan analisis serta berbagai buku dan artikel sebagai sumber data sekunder. Hasil penelitian ini menunjukkan bahwa penggunaan pronomina persona lebih dominan dibanding pronomina lainnya sebab pronomina ini berperan dalam mengembangkan karangan yang menarasikan manusia sebagai tokohnya. Kata Kunci: Pronomina, cerita fantasi, karangan siswa.